2017
DOI: 10.18203/2349-3291.ijcp20171459
|View full text |Cite
|
Sign up to set email alerts
|

Study on to assess pulmonary function test changes in asthmatic child using spirometry and its diagnostic and prognostic value

Abstract: Background: Asthma is a disease that has become increasingly common over the last century making it now one of the commonest chronic disorders in the world. Spirometric lung function tests are playing a key role in the diagnosis and management of asthma in children. Considering the usefulness of spirometer in the diagnosis of asthma and scarcity of the literature regarding the role of spirometer in the diagnosis of Asthma especially in Indian context, the present study was undertaken to assess pulmonary functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…Our study demonstrated that the degree of obesity in CP patients is correlated with an increased left ventricular wall thickness (IVSd and LVPWd). These results are consistent with several publications postulating that obesity is associated with interventricular wall and posterior wall thickness [31,35,36]. However, the observed positive correlation between BMI SDS and IVSd was stronger than the correlation between BMI SDS and LVPWd.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated that the degree of obesity in CP patients is correlated with an increased left ventricular wall thickness (IVSd and LVPWd). These results are consistent with several publications postulating that obesity is associated with interventricular wall and posterior wall thickness [31,35,36]. However, the observed positive correlation between BMI SDS and IVSd was stronger than the correlation between BMI SDS and LVPWd.…”
Section: Discussionsupporting
confidence: 93%
“…The left and right ventricular functions of all CP patients in our study, as determined by EF, FS, and TAPSE, were within the normal range, which indicated that all patients had a normal systolic function of both ventricles. These findings were supported by previous studies [27,30,35,36,40,41].…”
Section: Discussionsupporting
confidence: 91%